Implementation of Code Blue In Hospitals - Effendi, Rinal (Devotion : Journal of Research and Community Service, 2023)
Cardiac Arrest is a form of emergency due to malfunction of electrical waves in the heart that cause arrhythmias, so that the heart cannot pump blood to the brain, lungs, and other organs that can occur to anyone and at any time so that it needs proper and immediate treatment to be able to save the patient's life. In the case of hospitals, an activation code system to respond to cardiac arrest, called Code blue, was established to provide an appropriate, fast, and systematic Basic Life Support. The Code blue system was formed by the local hospital by establishing a code blue system, including code blue teams, BLS equipment and equipment, code blue activation through communication systems in hospitals, and regular education and training to ensure quality control. Cardiac Arrest treatment is the ability to be able to detect and react quickly and correctly to restore the heart rate to a normal condition as soon as possible to prevent brain death and permanent death, The patient's chances of survival are reduced by 7 to 10 percent every minute that runs without cardiopulmonary resuscitation and defibrillation